Implementasi Gerakan Literasi Sekolah Melalui Pemanfaatan Majalah Dinding Digital - Nurini, Nurini (Jurnal Didaktika Pendidikan Dasar, 2024)
Reading and writing as one of the literacy activities in a positive school culture becomes boring. It is challenging to increase students’ interest in literacy. To embody Ki Hadjar Dewantara’s philosophy, learning notices the nature of the times, the school literacy movement must utilize technology advances. This research aims to increase students’ interest in reading and writing and to determine digital media’s effectiveness in increasing literacy ability. This is a qualitative research approach. The data collection techniques are through observation and interview. The research subjects are fourth to sixth-grade students. First, they make a wall magazine, next teacher uploads it to Google Sites, then other students watch by the link provided. The research result shows that students get more enthusiastic than looking for reference sources to write. When they place it on a digital media with varied digital displays, student’s reading enthusiasm increases. Google Sites use as a form of digital media is suitable as an alternative solution for increasing students’ interest in reading and writing. It is also effective in increasing literacy ability. The research benefit provides real experiences and a meaningful learning process. Digital media provides easy access everywhere and makes publication widely spread.